The NFTI-QOL: A Disease-Specific Quality of Life Questionnaire for Neurofibromatosis 2 - Hornigold, Rachael E.; Golding, John F.; Leschziner, Guy; Obholzer, Rupert; Gleeson, Michael J.; Thomas, Nick; Walsh, Daniel; Saeed, Shakeel; Ferner, Rosalie E. (Journal of Neurological Surgery Part B: Skull Base, 2012)
The objective of this study was to develop a reliable, validated disease-specific score measuring quality of life (QOL) in clinical practice and treatment trials in Neurofibromatosis 2 (NF2) individuals. In NF2 patients, qualitative interviews (n = 15) and a focus group session (n = 30) generated items for a pilot questionnaire. This was tested and refined (n = 20). The final version (NFTI-QOL) was validated (n = 50) with two generic QOL questionnaires (SF-36 and EuroQOL). The NFTI-QOL was also administered to patients with solitary vestibular schwannoma (SVS) (n = 30) and normal controls (n = 30). The participants were NF2 patients, SVS patients, and normal controls. NFTI-QOL score, SF-36 score, and EuroQOL score were the main outcome measures. Mean NFTI-QOL score was 9.4 (range: 0 to 20, maximum possible score = 24). The NFTI-QOL score correlated strongly with EuroQOL (r = 0.71, p < 0.001) and SF-36 (r = 0.81, p < 0.001). NF2 individuals were significantly worse than the SVS patients, who in turn were worse than the controls on the NIFTI-QOL. The NFTI-QOL showed good internal reliability (Cronbach's α = 0.87). We developed an eight-item disease-specific QOL score for NF2 patients, validated against SF-36 and EuroQOL. It correlated strongly with clinician-rated disease severity in NF2, with better correlation than the SF-36 in this regard.
Keywords: NFTI-QOL; quality of life; neurofibromatosis 2; vestibular schwannoma; SF-36; EuroQOL